2018
DOI: 10.1042/bsr20180019
|View full text |Cite
|
Sign up to set email alerts
|

MiR-150-3p targets SP1 and suppresses the growth of glioma cells

Abstract: Glioma has been considered as one of the most prevalent and common malignancy of the nervous system; however, the underlying mechanisms that are responsible for the occurrence and development of glioma still remain largely unknown. Amounting evidence highlights the critical regulatory function of miRNAs in carcinogenesis. Here, we showed that the expression of miR-150-3p was significantly decreased in glioma tissues and cell lines. Suppressed expression of miR-150-3p was associated with the lymph node metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…After data analyses, a total of 26 miRNAs, 248 mRNAs, 1118 lncRNAs, and 382 circRNAs were differential between miR‐145‐5p mimics and NC groups. We noted both tumor suppressive and oncogenic miRNAs were included in the differentially expressed miRNAs, among which miR‐148b‐3p, miR‐150‐3p, miR‐2116‐3p, miR‐3940‐5p, miR‐4653‐3p, miR‐4701‐5p, miR‐4741, miR‐4749‐3p, miR‐4769‐3p, and miR‐663a are tumor suppressive miRNAs . Moreover, miR‐1539, miR‐1825, miR‐3151‐3p, miR‐550a‐3p, miR‐550a‐5p, and miR‐575 are oncogenic miRNAs .…”
Section: Discussionmentioning
confidence: 95%
“…After data analyses, a total of 26 miRNAs, 248 mRNAs, 1118 lncRNAs, and 382 circRNAs were differential between miR‐145‐5p mimics and NC groups. We noted both tumor suppressive and oncogenic miRNAs were included in the differentially expressed miRNAs, among which miR‐148b‐3p, miR‐150‐3p, miR‐2116‐3p, miR‐3940‐5p, miR‐4653‐3p, miR‐4701‐5p, miR‐4741, miR‐4749‐3p, miR‐4769‐3p, and miR‐663a are tumor suppressive miRNAs . Moreover, miR‐1539, miR‐1825, miR‐3151‐3p, miR‐550a‐3p, miR‐550a‐5p, and miR‐575 are oncogenic miRNAs .…”
Section: Discussionmentioning
confidence: 95%
“…The plasmids expressing miRNAs, which were treated by transient transfection, could remain stable from 0 to 72 h post trVLP infection with the same observation result of GFP under fluorescence microscope [ 37 , 38 ]. As for the miR-150-3p, its stability in cell culture has been confirmed in previous studies [ 39 , 40 ], which means it can provide sustained functions of affecting protein synthesis post trVLP infection. As shown in Figure 2 b, all the plasmid transfection was done 24 h before trVLP infection.…”
Section: Methodsmentioning
confidence: 58%
“…In contrast, miR-150-5p inhibits CD133-positive liver cancer stem cells 35 , functions as a tumor suppressor in colorectal cancer cells 36 , and suppresses triple-negative breast cancer metastasis 37 . In addition, miR-150-3p suppresses the growth of glioma cells by targeting SP1 55 , and induces apoptosis in pancreatic cancer cells 56 . In the present study, we demonstrated that the overexpression of both miR-150-5p and miR-150-3p inhibits OC growth and metastasis in vitro and in vivo, which combined with previous reports 57,58 strongly supports the tumor-suppressive effects of miR-150-5p/3p in OC.…”
Section: Discussionmentioning
confidence: 99%